KALIMAT SINDIRAN DALAM BAHASA JAWA DI YOGYAKARTA - , CANDRA DEWI SETYAWATI; , Prof. Dr. Marsono, S.U., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Language is a communication tool used by humans to communicate with others. Language is also used to express good feelings happy, sad or feeling of dislike toward others. Every spoken language also has a variety of meanings. At the District Depok, Sleman, Yogyakarta Java language is commonly used. Factors of age, sex, and education also affect language development allusions in this area. Research on innuendo sentence will be discussed on the form and purpose of satire sentence. Tense used satire satire marker word classification categories. A marker can be known with any insinuation current context of the spoken utterances. Later in this study, mean teasing sentence will be analyzed using semantic analysis. Semantic analysis used was the intent of the semantic analysis. Semantic analysis is used to determine the intent and meaning of spoken utterances mean.